Letter (copy) : Jesus & Julian Hickman Urrutia - Tewson, Vincent
027-0010-001 International HVT/AC/108 6th June, 1940. Señor J.I. de Lizaso, Basque Delegation, 14, Eccleston Sq., S.W. 1. Dear Señor Lizaso, JESUS & JULIAN HICKMAN URRUTIA. I have now learned from Mr. R. R. Stokes that he has made enquiries about the possibility of placing the above-named draughtsmen, but regrets that at the present time their services cannot be used. I am enclosing copy of his letter for your information. Yours sincerely, Assistant Secretary. 292/946/27/10